Feasibility Study of Daily Test Items for 5th Grade IPAS Based on Bloom's Taxonomy in Elementary School - Rosmawati, Eka; Wulandari, Bunga Ayu; Widowati, Atri (Journal of Innovation and Research in Primary Education, 2025)
This study aims to analyze the feasibility of the fifth-grade IPAS daily test questions at SD Negeri 153/X Harapan Makmur based on Bloom’s Taxonomy. This research employs a qualitative descriptive method using document analysis, interviews, and observations. "A total of two IPAS teachers were interviewed and observed to support data triangulation." The primary data consists of 120 daily test questions, categorized into LOTS (Lower Order Thinking Skills) and HOTS (Higher Order Thinking Skills). The findings reveal that 81.7% of the questions fall into the LOTS category, while only 18.3% qualify as HOTS, with the majority at the analyzing (C4) level (72.7%), while evaluating (C5) and creating (C6) comprise only 18.2% and 9.1%, respectively. Interviews with teachers indicate that the main challenges in designing HOTS questions are a lack of training, time constraints, and difficulties in creating assessment rubrics. Therefore, improving teachers’ competence through HOTS question development training and the creation of a HOTS-based question bank is crucial to enhancing the quality of learning assessment.